THE WAYS OF IMPROVING SPEAKING SKILLS IN ESP CLASSES (INFORMATION TECHNOLOGY) (Scientific journal of the Fergana State University, 2024)
English for specific purposes (ESP) refers to the teaching and learning of English language skills in a specific context or for a specific purpose. It is widely used in spheres such as IT, business, tourism, medicine, or engineering. This approach to language instruction focuses on developing the language skills and vocabulary needed for a particular field or profession, rather than on general language proficiency. Therefore, it is crucial to develop the language skills to prepare highly qualified specialists in various spheres of life. This article is devoted to enhancing speaking skills in ESP groups.